Importance of coarse‐mode nitrate produced via sea salt as atmospheric input to East Asian oceans - Syuichi Itahashi; Hiroshi Hayami; Itsushi Uno; Xiaole Pan; Mitsuo Uematsu (Geophysical Research Letters)
Abstract The atmospheric input of anthropogenic total reactive oxygenated nitrogen (NOy) to ocean regions in East Asia during 2002–2004 was revisited with an updated regional chemical transport model and the latest emissions inventory. The updated model treats both fine‐ and coarse‐mode nitrate (NO3−). Coarse‐mode NO3− is produced by the reaction of nitric acid (HNO3) and sea salt particles. The modeling system reproduced the atmospheric concentration and wet deposition amount of NO3− quantitatively compared with observations. The fraction of coarse‐mode NO3− was also well captured. NOy deposition amounts over marginal seas and open oceans were 733 and 730 Gg N/yr, which are increases of 1.6‐ and 2.2‐fold, respectively, by including coarse‐mode NO3−. Anthropogenic NOx emissions from China were 5377 Gg N/yr, and 3060 Gg N/yr was exported from China; therefore, the NOy deposition amount over ocean regions in East Asia (1463 Gg N/yr) corresponded to almost half (48%) of the export amounts.